S6D:6 Inhibition of eif4a translation initiation ameliorates lupus manifestations. (21st March 2018) - Morell, M; Gómez-Hernández, G; Varela, N; Alarcón-Riquelme, M
Abstract : Systemic Lupus Erythematosus (SLE) is an autoimmune disease characterised by loss of tolerance and presence of auto reactive B and T cells. Pathogenic mechanisms of the disease are still unclear and clinical manifestations are heterogeneous complicating diagnosis and disease treatment. Several organs can be affected such as skin, joints, central nervous system, and kidneys. Current treatments include corticosteroids and immunosuppressive drugs, nonsteroidal anti-inflammatory drugs, antimalarials and other biologicals such as belimumab or rituximab. During the last decades mouse models have been very helpful to understand lupus pathogenesis and to test the efficacy of SLE therapies. In this work we evaluated the therapeutic potential of inhibiting the translation initiation process with Pateamine A, a natural compound isolated from a marine sponge, in a lupus preclinical model. Translation initiation via the eIF4E complex is a key step in cytokine and antibody production, and its inhibition has been successful in cancer models. Pateamine A has anti-proliferative and immunosuppressive activities. In the BXSB.Yaa strain, we tested the efficiency of Pateamine A in controlling lupus autoimmune symptoms and neurological complications. Animal treatment started when first signs of disease were present (12 weeks) and finished at the time in which the strain has a mortality rate of 50% (5 months). Our data shows that Pat A treatment reduces circulating levels of proinflammatory cytokines and autoantibodies increasing survival. An improvement in cognitive functions in treated animals was also observed with neural behaviour tests (learning/memory, and depression) together with a reduction of proinflammatory cytokines in the hippocampus. We did not observe any side effects of the treatment. Alltogether our data suggests that inhibition of translation initiation has an effect in controlling disease activity at the immunological and neurological levels and open a new line of research for strategies to treat lupus and other autoimmune diseases based on the inhibition of translation at early stages.